2017
DOI: 10.1002/jcp.26245
|View full text |Cite
|
Sign up to set email alerts
|

The MIP‐1α autocrine loop contributes to decreased sensitivity to anticancer drugs

Abstract: Several autocrine soluble factors, including macrophage inflammatory protein-1α (MIP-1α), tumor necrosis factor-α, and hepatocyte growth factor, promote cell survival and growth in multiple myeloma (MM) cells. We hypothesized that inhibition of the MIP-1α autocrine loop may enhance the cytotoxic effect of anticancer drugs in MM cell lines. In the present study, an MIP-1α neutralizing antibody suppressed cell proliferation and enhanced the cytotoxic effect of melphalan or bortezomib on MM cells. In addition, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…ERK1/2 and Akt activation are known to regulate the expression of many apoptosis-controlling factors. Up-regulation of pro-apoptotic factors such as Bax and Bim and down-regulation of anti-apoptotic factors such as Bcl-2 and Bcl-xL leads to caspase activation and apoptosis [37][38][39][40][41]. In this study, MEK inhibitor suppressed Bcl-2 and Bcl-xL expression and enhanced Bax and Bim expression in MEK inhibitor-sensitive cells but did not affect expression of any of the proteins in MEK inhibitor-resistant cells.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…ERK1/2 and Akt activation are known to regulate the expression of many apoptosis-controlling factors. Up-regulation of pro-apoptotic factors such as Bax and Bim and down-regulation of anti-apoptotic factors such as Bcl-2 and Bcl-xL leads to caspase activation and apoptosis [37][38][39][40][41]. In this study, MEK inhibitor suppressed Bcl-2 and Bcl-xL expression and enhanced Bax and Bim expression in MEK inhibitor-sensitive cells but did not affect expression of any of the proteins in MEK inhibitor-resistant cells.…”
Section: Discussionmentioning
confidence: 45%
“…LoVo and Colo-205 cells with acquired resistance to PD0325901 (LC Laboratories, Woburn, MA, USA) or trametinib (LC Laboratories) (LoVo/PR, Colo-205/PR and LoVo/TR) were generated as previously described [37,[51][52][53][54][55].…”
Section: Cell Culturementioning
confidence: 99%
“…P values of < 0.05 were regarded significant. Drug interactions were measured based on the combination index (CI), as previously described [24,39].…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 and Bcl-XL, a member of anti-apoptotic Bcl-2 family proteins, suppress apoptosis by involving mitochondrial outer membrane permeability [19], yet inhibitor of apoptosis (IAP) family proteins do so by inhibiting caspase activity [20,21]. Most anti-cancer drugs suppress tumor proliferation by inducing apoptosis, hence the overexpression of anti-apoptotic proteins results in drug resistance [22][23][24][25]. To understand drug resistance, further studies are required on the underlying intracellular signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…*P < 0.01 vs. RPMI8226 untreated cells, # P < 0.01 vs. RPMI8226/L-PAM untreated cells (ANOVA with Dunnett's test) inflammatory protein 1α (MIP-1α) or tumor necrosis factor α (TNFα) promote c-Src activation via binding to specific receptors in cancer cells [41]. In addition, activation of ERK1/2, Akt, and/or NF-κB by MIP-1α and/or TNFα autocrine loop is associated with melphalan resistance in MM cells [40,42]. These findings indicated that activation of ERK1/2, Akt, and NF-κB contributes to melphalan resistance in MM cells.…”
Section: Discussionmentioning
confidence: 99%